2017
DOI: 10.3390/genes8110302
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Repetitive Elements on the Y Chromosome Formation in Plants

Abstract: In contrast to animals, separate sexes and sex chromosomes in plants are very rare. Although the evolution of sex chromosomes has been the subject of numerous studies, the impact of repetitive sequences on sex chromosome architecture is not fully understood. New genomic approaches shed light on the role of satellites and transposable elements in the process of Y chromosome evolution. We discuss the impact of repetitive sequences on the structure and dynamics of sex chromosomes with specific focus on Rumex acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 76 publications
2
33
0
Order By: Relevance
“…These results suggest that the SDRs of these two species were established relatively recently, which is a common feature of the sex chromosomes of the Salicaceae species studied so far (Geraldes et al , 2015; Pucholt et al , 2017; Zhou et al , 2018, 2020). Along with this, our results also suggest that the Y and W chromosomes have expanded in content, a pattern that is common in young sex chromosomes of plants (Hobza et al , 2015, 2017). Moreover, our results simultaneously showed that the Salicaceae exhibit an extremely fast rate of sex-chromosome turnover.…”
Section: Discussionsupporting
confidence: 81%
“…These results suggest that the SDRs of these two species were established relatively recently, which is a common feature of the sex chromosomes of the Salicaceae species studied so far (Geraldes et al , 2015; Pucholt et al , 2017; Zhou et al , 2018, 2020). Along with this, our results also suggest that the Y and W chromosomes have expanded in content, a pattern that is common in young sex chromosomes of plants (Hobza et al , 2015, 2017). Moreover, our results simultaneously showed that the Salicaceae exhibit an extremely fast rate of sex-chromosome turnover.…”
Section: Discussionsupporting
confidence: 81%
“…These translocations and other structural rearrangements may also suppress recombination and cause linkage between autosomal and sex-linked genes [2]. In plants, the large sizes of young Y chromosomes have been attributed to the accumulation of retrotransposons (reviewed in [29]).…”
Section: Discussionmentioning
confidence: 99%
“…Peichel, personal communication; see also Chalopin, Volff, Galiana, Anderson, & Schartl, 2015;Hobza et al, 2017). As a definitive validation of our model, it would be worthwhile to determine the number of alignment sites of DNA segments representative of our HIDRs in a future Y chromosome assembly.…”
Section: Hidr Snpsmentioning
confidence: 99%